Cancer statistics in Kamrup urban district: Incidence and mortality in 2007-2011. - Sharma, Jagannath Dev; Kataki, Amal Chandra; Barman, Debanjana; Sharma, Arpita; Kalita, Manoj (Indian Journal of Cancer)
Purpose: The aim of this study was to report cancer statistics in Kamrup Urban District, including incidence and, mortality.Introduction: In the last five year PBCR-Guwahati witnessed a remarkable growth in cancer incidence cases. The number of new cases of all cancer was increased from 155.3 to 188.5 and 102.7 to 165.3 per 100,000 men and women respectively from the year 2007 to 2011 in KUD. The data from KUD also have shown that for some of the specific types of cancer are highest or some of the highest incidence in rates in the world; particularly cancers of upper aero-digestive tract consist of anatomical sites such as oral cavity, hypopharynx, larynx gallbladder, stomach, lung, prostate and oesophageal cancer.Materials and Methods: Age-standardized rates (ASR) (per 100,000 person-years) for incidence, mortality were calculated using the World Standard Population as proposed by Segi and modified by Doll et al. Descriptive statistics were presented by tables and figures.Results: A total of 6623 number of cases (male = 3809, female = 2814) were diagnosed with cancer in the last five years (2007-2011) period of time. The overall age standardized cancer incidence rate is almost 21% higher in men than in women. The pooled ASR for the five year period is 175.2 and 144.7 per 100,000 men and women.Conclusion: Overall cancer incidence and mortality rates have increased since 2007.